An interprofessional collaboration between medicine and pharmacy schools: Designing and evaluating a teaching program on practical prescribing - Mohammad Reza Javadi; Mina Khezrian; Anahita Sadeghi; Seyed Hossein Hajimiri; Kaveh Eslami (Wolters Kluwer Medknow Publications, 2017)
Objective: Medical students need proper education in drug prescription. The aim of the present study is to introduce a course that improves the students' prescribing skills and also promotes an interprofessional collaboration between medicine and pharmacy schools. Methods: This study was done in a skill laboratory at the pharmacotherapy department of Tehran University of Medical Sciences, Tehran, Iran. The course was an 18-h interactive workshop in 3 days under the supervision of clinical pharmacists. A total of 18 medical students participated in these classes before their internship. Before and after each class, they were given tests and paired t-test was done to compare the marks. Findings: A total of 18 medical students participated in this study. The results showed that the knowledge of the students on pharmacotherapy, drug information, and prescribing skills has been significantly improved at the end of the course. Conclusion: Using clinical pharmacists to the present pharmacotherapy course could be an effective model for medical students to obtain better prescribing skills.